From “State Monopoly” to “Regulatory State” in the Energy Sector : An Analysis of Thai Constitutional Court Ruling No. 1/2566 and Lessons from the Energy Transition of the French Republic - KRABUANSRI, ANAN (Journal of Thai Ombudsman, 2026)
This article aims to analyze the legal status of “electricity generation” within the Thai legal system following Constitutional Court Ruling No. 1/2566. It conducts a comparative study with the evolution of French energy law, commencing with Law No. 2000 - 108 of 10 February 2000 on the Modernization and Development of the Public Electricity Service This Act served as the foundational legislation for reform before being systematically codified into the current Energy Code. Furthermore, the study aims to demonstrate the paradigm shift in the State’s role from an “Operator State” or “State Monopoly” to a “Regulatory State” within the context of public economic law, amidst debates on the legal legitimacy of reducing state ownership in the electricity generation sector to below 51 percent. The findings reveal, firstly, that the Thai Constitutional Court interpreted that “electricity generation” does not constitute a basic utility or network requiring a state monopoly under Section 56 of the Constitution, which aligns with the international principle of “Unbundling” found in the French legal system. This principle legally distinguishes “generation” as a competitive activity from “network operation,” which remains a natural monopoly. Secondly, the study confirms that such a transformation does not constitute an abandonment of state duties; rather, it reflects the concrete status of a Regulatory State. In this model, the State focuses on maintaining energy security through regulatory mechanisms via an independent regulator (ERC) and strategic planning (PDP), instead of maintaining traditional ownership over the means of production.